Money in Islam: The Siyasah Shar‘iyyah’ Perspective and Implementation Strategy - Bedjo Santoso (Tazkia Islamic Finance and Business Review, 2012)
Objective – The idea of revisiting the currency and gold dinar in Islamic view is an interesting discuss in the current monetary system. This study therefore investigated the gold as currency in Islamic view. The survey includes historical aspect, supremacy of gold currency and the weakness of fiat money by employed maslahah-mursalah approach. Besides that, the study discussed law of gold as money in light maqashid sharia , and Siyasah Syar’iyya approach, determine the obstacles and barriers to gold dinar implementation on the current economic system and toprovide appropriate model and stepping strategy to implement gold dinar as currency in the society.Method –This study is a qualitative approach based on issues that have been raised. Deductive method is considered as an appropriate method to explore the implementation of gold currency. This is because it requires a comprehensive discussion on the collected data to develop an appropriate model. This research employed historical study and library research.Result – The review declared that gold coins as money served ‘maslahah ’. However, it is difficult to implement due to some obstacles. Stepping is necessary to avoid chaos condition. Numerous obstacles are taken place. It takesat least15years and it could be startedby educating people. Then is followed by gold in the domestic transaction that backed-up by information/communication technology. Involving the Cooperatives model also can be the best model. However, radical way is not appropriate as it faces a challenge from IMF in the Article IV, part 2 (b) (i), and therefore political support is needed.Conclusion – The initial using gold / silver as money is permissible. Nevertheless, the ruling is subject to change when the government wants to print its own currency. If the primary objective of the printing is to complete the implementation of the Sharia laws which have been charged to them (especially the law with respect to currency such as zakat, kanzul mall, hudud, diyat, sarf, etc.) As well as to protect the entire territory from the possibility that the use of foreign currency may harm the economy of its people, then the ruling becomes mandatory .Keywords : Fiat Money, Gold Money, Monetary System, Siyasah Shar’iyah